Millennial students’ perception on the integration of Islam and science in Islamic universities - Rizkia Suciati; Herawati Susilo; Abdul Gofur; Umie Lestari; Izza Rohman (IAIN Salatiga, 2022)
This study describes students' perception of the concept of the integration of Islam and science. The integration of religious knowledge into science learning means the elimination of the paradigm of separating science and religion. This is important because many students do not understand how to connect the scientific theories studied to their own religious beliefs. This research surveys 175 students from 4 Islamic universities in Indonesia. The respondents filled an online questionnaire containing 8 two-tiered questions based on 7 conceptual understanding indicators of the integration of Islam and science. The indicators measure students’ understanding of: (1) Science; (2) The relationship between science and religion (Islam); (3) The effect of science on religion; (4) The influence of Islamic insights on science learning; (5) The role of religion in the development/advancement of science; (6) The conflict between science and religion; (7) The differences in scientific concepts developed by Muslim and non-Muslim scientists. The result shows that the students’ perception on the relationship between Islam and science can be categorized as the perception of integration. They argue that religion has a role in the development of science, and science has a role in supporting the sustainability of life. The students also conceive that a lecturer's Islamic insight can have an influence on the learning process, especially in Biology course.